Detection of perfluoroalkyl acids and sulphonates in Italian eel samples by HPLC-HRMS Orbitrap. (February 2018) - Chiesa, Luca Maria; Nobile, Maria; Pasquale, Elisa; Balzaretti, Claudia; Cagnardi, Petra; Tedesco, Doriana; Panseri, Sara; Arioli, Francesco
Abstract: Perfluoroalkyl substances (PFASs) contain one or more carbon-bound hydrogens substituted by fluorine. Since the 1950s, these compounds have been used to manufacture fat- and water-resistant fabrics, paper and food containers, and to produce photographic films, firefighting foams, detergents and insecticides. The widespread use and global distribution of PFASs, have led to their accumulation in the environment. Food, particularly fish and other seafood, is considered the main route of human exposure to PFASs. Consequently, the European Food Safety Authority (EFSA) recommends that more data be collected, to build a database on the contamination levels of the individual PFASs in food, to evaluate a reliable chronic risk to the European consumers. This requires high-sensitivity analytical methods, to increase the number of quantifiable samples and, thereby, improve the credibility of exposure assessments. In this context, the aim of the present research is to develop and validate a sensitive and specific method based on high-performance liquid chromatography-high resolution mass spectrometry (HPLC-HRMS) analysis, to monitor the presence of 16 PFASs in Italian eels ( Anguilla anguilla ) from the Italian Lake Garda. The detection limits (CCα) and detection capability (CCβ) in the order of pg g −1, the recoveries between 80 and 101% and the other validation parameters fulfilled the requirements of Commission Decision 657/2002/EC. The identification and quantification of PFASs, up to 11 in the same sample, showed a similar distribution among 90 eels. Perfluorooctane sulphonic acid (PFOS) and perfluorobutanoic acid (PFBA) were the analytes more frequently found in the eel samples (94 and 82%, respectively). Graphical abstract: Image Highlights: Perfluoroalkyl substances (PFASs) accumulate in environment and in human through diet. One sensitive HPLC-HRMS method for PFASs in eels is reported. Eels from the Lake Garda in North Italy were analysed. Up to eleven PFASs were contemporaneously detected in several eel samples.